PENEGAKAN HUKUM DALAM TINDAK PIDANA LINGKUNGAN HIDUP MENURUT UU NO. 18 TAHUN 2004 TENTANG PERKEBUNAN - HASUDUNGAN P. SIDAURUK, SH A.2120025, Jurnal Mahasiswa S2 (Jurnal NESTOR Magister Hukum, 2013)
AbstractThis thesis discusses the duality of powers between the investigators and investigators Plantation Environment in law enforcement against corporate crime combustion of oil palm plantations on land preparation period in Sambas district. In addition, it also has a goal is to reveal and analyze the causes of the dualism of authority between investigators and investigators Plantation Environment in law enforcement against corporate crime combustion of oil palm plantations on land preparation period in Sambas district and solutions to prevent it.Through empirical legal research methods with socio-juridical approach the conclusion, that the causes of the dualism of authority between investigators and investigators Plantation Environment in law enforcement against corporate crime combustion of oil palm plantations on land preparation period in Sambas district of Sambas district is as following: (a) The existence of overlapping authority arrangements regarding the investigation by criminal investigators in clearing land by burning the plantation is regulated by Law No. 18 Year 2004 on Plantation and Law No. 32 of 2009 on Environmental Protection and Management life; (b) The existence of sectoral ego attitude of each of the investigators because they were given the authority to conduct investigations by law, so that the investigators felt each have the authority to open a criminal investigation against plantation land by burning, and (c) less maximal Police Investigator role in coordination and supervision of investigators and investigators Environment Plantations, thus resulting in the emergence of the problem of dualism of authority in conducting the investigation of the offenses opened plantations by burning. As a solution to prevent the dualism of authority between investigators and investigators Plantation Environment in law enforcement against corporate crime combustion of oil palm plantations on land preparation period in Sambas district is to takeover the investigation of criminal cases in the plantation environment by Police Investigator .This is possible because, according to Article 45 paragraph (1) of Law No. 18 Year 2004 on Oil and Article 94 of Law No. 32 of 2009 on the Protection and Management of the Environment stated that: in addition to investigating officers at the Indonesian National Police, the Servants particular civil investigators in this case the scope of their respective duties on the plantation areas and / or areas of environmental protection and management was given special authority as investigators. In addition, the duties and responsibilities of investigators under the coordination and supervision of the police investigators.2AbstrakTesis ini membahas tentang dualisme kewenangan antara PPNS Perkebunan dan PPNS Lingkungan Hidup dalam penegakan hukum terhadap korporasi yang melakukan tindak pidana pembakaran lahan perkebunan sawit pada masa persiapan lahan di Kabupaten Sambas.Di samping itu juga mempunyai tujuan yaitu untuk mengungkapkan dan menganalisis sebab-sebab terjadinya dualisme kewenangan antara PPNS Perkebunan dan PPNS Lingkungan Hidup dalam penegakan hukum terhadap korporasi yang melakukan tindak pidana pembakaran lahan perkebunan sawit pada masa persiapan lahan di Kabupaten Sambas dan solusi untuk mencegahnya.Melalui metode penelitian hukum empiris dengan pendekatan yuridis sosiologis diperoleh kesimpulan, bahwa sebab-sebab terjadinya dualisme kewenangan antara PPNS Perkebunan dan PPNS Lingkungan Hidup dalam penegakan hukum terhadap korporasi yang melakukan tindak pidana pembakaran lahan perkebunan sawit pada masa persiapan lahan di Kabupaten Sambas Kabupaten Sambas adalah sebagai berikut: (a) Adanya tumpang tindih pengaturan mengenai kewenangan penyidikan yang dilakukan oleh PPNS dalam tindak pidana membuka lahan perkebunan dengan cara membakar yang diatur oleh Undang-undang Nomor 18 Tahun 2004 tentang Perkebunan dan Undang-undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup; (b) Adanya sikap ego sektoral dari masing-masing PPNS karena diberi kewenangan untuk melakukan penyidikan oleh undang-undang, sehingga masing-masing PPNS merasa memiliki kewenangan untuk melakukan penyidikan terhadap tindak pidana membuka lahan perkebunan dengan cara membakar; dan (c) Kurang maksimalnya peran Penyidik Polri dalam melakukan koordinasi dan pengawasan terhadap PPNS Perkebunan dan PPNS Lingkungan Hidup, sehingga mengakibatkan timbulnya masalah dualisme kewenangan dalam melakukan penyidikan terhadap tindak pidana membuka lahan perkebunan dengan cara membakar.Adapun solusi untuk mencegah terjadinya dualisme kewenangan antara PPNS Perkebunan dan PPNS Lingkungan Hidup dalam penegakan hukum terhadap korporasi yang melakukan tindak pidana pembakaran lahan perkebunan sawit pada masa persiapan lahan di Kabupaten Sambas adalah dengan pengambilalihan penyidikan terhadap perkara tindak pidana lingkungan hidup di lahan perkebunan oleh Penyidik Polri. Hal ini dimungkinkan karena menurut Pasal 45 ayat (1) Undang-undang Nomor 18 Tahun 2004 tentang Perkebunan dan Pasal 94 Undang-undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup dinyatakan bahwa: selain Penyidik Pejabat Kepolisian Republik Indonesia, maka Pejabat Pegawai Negeri Sipil tertentu, dalam hal ini PPNS yang ruang lingkup tugasnya masing-masing pada bidang perkebunan dan/atau bidang perlindungan dan pengelolaan lingkungan hidup diberi wewenang khusus sebagai penyidik. Selain itu, tugas dan tanggung jawab PPNS di bawah koordinasi dan pengawasan Penyidik Polri.